2021
DOI: 10.1111/jch.14400
|View full text |Cite
|
Sign up to set email alerts
|

Practical applicability of genetics for the prevention and treatment of hypertension

Abstract: Zou and colleagues are publishing in this issue of The Journal of Clinical Hypertension, result of one of their studies in which they found that human corin genetic polymorphisms is involved in blood pressure control, more specifically in salt sensitivity.It is being published in this journal shortly after a literature review indicated another 18 genes were also involved in salt sensitivity, however corin gene. This dynamism of This is an open access article under the terms of the Creative Commons Attribution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…In agreement with a renal corin function in sodium homeostasis, increased renal corin levels have been observed in rats and humans on high-salt diets, possibly indicating a compensatory response to increase sodium excretion [65]. Another recent study in humans identified an association between CORIN variants and salt sensitivity, longitudinal blood pressure changes, and hypertension incidence [66,67]. In rat models of kidney injury and severe cardiorenal syndrome, low levels of renal corin were reported [47,68].…”
Section: Functional Significance Of Renal Corin Expressionmentioning
confidence: 57%
“…In agreement with a renal corin function in sodium homeostasis, increased renal corin levels have been observed in rats and humans on high-salt diets, possibly indicating a compensatory response to increase sodium excretion [65]. Another recent study in humans identified an association between CORIN variants and salt sensitivity, longitudinal blood pressure changes, and hypertension incidence [66,67]. In rat models of kidney injury and severe cardiorenal syndrome, low levels of renal corin were reported [47,68].…”
Section: Functional Significance Of Renal Corin Expressionmentioning
confidence: 57%